From apprenticeship to higher education : navigating the credential landscape - Dismore, Harriet [Verfasser] (My University, 2014)
"The credential landscape of vocational and higher education in the UK has expanded in recent years, alongside a rise in the number of students undertaking qualifications and a steady increase in tuition fees. The transition from an apprenticeship to higher education is one example of the progression from vocational to higher education. However, the ways in which this pathway is navigated according to the students who have followed this route have received little attention. This paper focuses on the examples of four students in England who each progressed to higher education with different qualifications. Drawing on Archer's concept of reflexivity, the analysis revealed three important factors for negotiating transition. These were firstly the credential landscape itself, secondly how their employer perceived higher education qualifications and thirdly how higher education institutions perceived vocational qualifications. The findings illustrate how students confronted and overcame the various constraints and barriers in order to pursue higher education." (Publisher; BIBB-Doku)
Keywords: S 4.3.5 Bildungsbeteiligung & soziale Gerechtigkeit; S 1.4 Hochschulbildung; I 2.2.1 Westeuropa; Durchlässigkeit im Bildungssystem; Berufsbildung; Hochschulbildung; Hochschulzugang; Nicht traditionell Studierender; Großbritannien